2022
DOI: 10.1200/jco.21.02864
|View full text |Cite
|
Sign up to set email alerts
|

Age of Onset of Receptor Tyrosine Kinase Fusions Drives Distinct Biologic Outcomes in Thyroid Cancer

Abstract: A third possibility to explain the distinct age-dependent biologic consequences of RET and NTRK fusions may ASSOCIATED CONTENT See accompanying article on page 1081Author affiliations and support information (if applicable) appear at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(14 reference statements)
1
0
0
Order By: Relevance
“…In addition, an interesting tendency between the incidence of fusion oncogenes and age was observed: the younger the patients were, the higher the incidence of fusion oncogenes. Of note, when patients were subgrouped by the age of 20 years, it was found that pDTCs (years <20) had a higher incidence of fusion oncogenes (45.2% vs 25.5%) but a lower incidence of BRAF mutations (19.4% vs 49.5%) than their adult counterparts, which is concordant with previous literature ( 47 , 58 , 59 ).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, an interesting tendency between the incidence of fusion oncogenes and age was observed: the younger the patients were, the higher the incidence of fusion oncogenes. Of note, when patients were subgrouped by the age of 20 years, it was found that pDTCs (years <20) had a higher incidence of fusion oncogenes (45.2% vs 25.5%) but a lower incidence of BRAF mutations (19.4% vs 49.5%) than their adult counterparts, which is concordant with previous literature ( 47 , 58 , 59 ).…”
Section: Discussionsupporting
confidence: 90%